Effect of CR, DER, and TATO on Profit Growth in Pharmaceutical Companies Listed on IDX - Harry Patuan Panjaitan; Daud Alfinas (Institut Bisnis dan Teknologi Pelita Indonesia, 2020)
This study aims to determine the influence of Current Ratio, Debt to Equity Ratio, and Total Assets Turnover on Profit Growth in pharmaceutical sub-sector manufacturing companies which were listed on Indonesia Stock Exchange in 2014-2018. The sample consisted of 9 pharmaceutical companies which were obtained using purposive sampling method. This study used multiple linear regression analysis and SmartPLS 3. The results showed that Current Ratio and Debt to Equity Ratio do not have significant influence on Profit Growth. Meanwhile, Total Assets Turnover has a significantly negative influence on Profit Growth.